2016
DOI: 10.1177/0022002715590877
|View full text |Cite
|
Sign up to set email alerts
|

Conscription, Inequality, and Partisan Support for War

Abstract: While recent scholarship suggests that conscription decreases support for military action, we argue that its effect is contingent both on a draft's consequences for inequality in military sacrifice and on partisanship. In an experiment examining public support for defending South Korea, we find that reinstating the draft significantly decreases support for war among Democrats; however, this effect is diminished if the draft reduces inequality in sacrifice. Support for war among Republicans, by contrast, respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 51 publications
1
17
1
Order By: Relevance
“…The differences are significant for all three samples in the first experiment, and for the Facebook sample in the second. On the other hand, average treatment effects in our convenience samples were often far from-and generally smaller than-the representative sample We reverse the polarity of the (Kriner and Shen 2016) experiment, estimating the effect of an all-volunteer force rather than the effect of the draft.…”
Section: Replicating Survey Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences are significant for all three samples in the first experiment, and for the Facebook sample in the second. On the other hand, average treatment effects in our convenience samples were often far from-and generally smaller than-the representative sample We reverse the polarity of the (Kriner and Shen 2016) experiment, estimating the effect of an all-volunteer force rather than the effect of the draft.…”
Section: Replicating Survey Experimentsmentioning
confidence: 99%
“…In each country, our surveys sought to replicate several experiments conducted on nationally representative samples. In the United States, we replicate experiments examining support for home mortgage interest subsidies via tax breaks versus cash payments (Haselswerdt and Bartels 2015); support for a hypothetical military intervention along the Korean border under the current all-volunteer force, versus a reinstatement of the draft (Kriner and Shen 2016); and belief that too much money is being spent on “welfare,” as opposed to “assistance for the poor” (Berinsky, Huber and Lenz 2012). The first two experiments were administered online to nationally representative samples by YouGov Polimetrix, while the third was part of the 2014 GSS cross-section, involving face-to-face interviews.…”
Section: Replicating Survey Experimentsmentioning
confidence: 99%
“…There was substantial and significant heterogeneity, Q (8) = 27.06, p < 0.001, I 2 = 65%, T = 0.09, T 2 = 0.01. McGinty et al [80] Kriner, Strike [79] Kriner, Troops [79] Cornwell & Krantz 2 [19] Andersen [67] Aklin et al [78] Walker et al [77] Stokes et al [76] Rickard et al, Singapore Sample [87] Rickard et al, US Sample [87] McCright [90] Kaplowitz et al, Main [75] Kaplowitz et al, Pilot [75] Dragojlovic et al [22] environment Chen et al [88] Zhou et al [86] Wen et al [85] Scully et al, Alcohol Tax [68] Scully et al, Ban SSB Sponsorship [68] Scully et al, Ban Alcohol Sponsorship [68] Scully et al, Sugar Tax [68] Reynolds et al, 2 [8] Reynolds et al, 1 [8] Rahn et al [84] Ortiz et al [21] Niederdeppe [89] Niederdeppe et al, Pain Medication [20] Niederdeppe et al, Alcohol [20] Niederdeppe et al, Soda [20] Niederdeppe et al [23] Gollust et al [82] Gollust et al [83] Bigman et al [15] Bergan [81] health Excluding studies that had confounded interventions resulted in k = 11 effect sizes and N = 5870. There was no funnel plot asymmetry and therefore trim and fill was not used.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Another study by Choi and James (2008) utilize dyadic data spanning 1950 through 1992, and find that conscription actually has a restraining effect on a nation's involvement in conflict, which contradicts their results of 2003 study. Results from studies such as those conducted by Horowitz and Levendusky (2011) and Kriner and Shen (2016) indicate that the introduction of conscription leads to lower public support for a nation's involvement in conflict, based on their experimental surveys.…”
Section: Military Recruitment Types and Warmentioning
confidence: 99%
“…On the other hand, voluntary soldiers may be too small in number for initiating military disputes (Choi and James 2003). Nonetheless, experimental research has shown that conscription leads to lower public support for participation in conflicts (Horowitz and Levendusky 2011;Kriner and Shen 2016). This means that, as opposed to countries with voluntary recruitment, voters in countries with conscription-based recruitment feel there is a higher chance that they or their own relatives might be involved in an armed conflict, causing voters in these countries to be more cautious about going to war.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%